Breeding For Disease Resistance in Farm Animals, (3rd Edition) - Bishop, Stephen C (CABI, 2014)
This chapter summarizes and updates our current understanding of the immune systems of farm animal species. It highlights the relatively recent understanding that innate immune responses are specific to classes of pathogen and drive downstream adaptive immune responses, critical for immunological memory. Examples are given where dis- ease resistance has been shown to involve immune mechanisms and, in a few cases only to date, genes that encode molecules involved in immune responses. The concept of increased immune robustness to challenge a wide range of pathogens, by selecting for increased innate immune responsiveness, is also discussed. Our ability to understand immune responses in farm animal species and to map genes involved in disease resist- ance has improved greatly with the availability of genome sequences for these species and the accompanying post-genomic technologies. The current challenge is to deal with the consequent data deluge, but prospects for breeding for disease resistance at the level of the immune response are exciting.